Helplessness or self care? : a study of nursing practice with depressed patients in an in-care setting : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Nursing Studies at Massey University - Butterfield, Shona (Massey University, 1982)
This study was conducted to investigate the practice of nurses when working with depressed patients in an in care setting. A survey of the literature shows that the role commonly prescribed for nurses who work in psychiatric settings is one that emphasises a one-to-one relationship based on models of psychotherapy and focusses on individual illness, pathology, symptoms and psycho-dynamics. It is suggested that this is not a role which most nurses working in New Zealand psychiatric settings would be able to implement in practice. Three perspectives of nursing practice were explored in the study: what nurses were seen to do in practice; what they thought they should do as evidenced in results of an exercise to rank different possible interventions; and what patients said were helpful nursing interventions. A framework was developed for the study which depicts the process of helplessness (depression) as the negative 'mirror-image' of the process of self care. Results were analysed within this framework to determine whether or not nurses tended to support behaviours which were indicative of movement towards helplessness or encourage those which indicated progress towards self care. Results suggest that nurses in this study sample did not encourage progress towards self care by their interventions. There was little evidence of positive reinforcement for independent or coping behaviours with patients in the study sample. Further, the nursing practice showed little relationship to the role prescribed in the literature. The nurses did demonstrate a warm, caring, friendly approach that seemed to stem from a more traditional 'succouring' or 'mothering' view of the nurse's role.
Keywords: Psychiatric nursing; Depression, Mental